Method for preparing ceramsite sand based on blast furnace slag, kaolin and red clay
Through the combination of blast furnace slag, kaolin and red clay, ceramic sand is prepared, which solves the high cost of oil fracturing proppant and blast furnace slag treatment problems, and provides low-cost, low-density, high compressive strength and high temperature resistance ceramics Grain sand meets the demand for oil fracturing and deals with the blast furnace slag resource utilization problem.
Patent Information
- Application Number
- CN202411313111.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
Existing petroleum fracturing proppant materials such as quartz sand, ceramic granules and coated proppants have problems in the oil industry, such as high cost, high density, poor flow diversion capacity and complex manufacturing processes, and it is difficult to meet the strength and density of petroleum fracturing. , high temperature resistance and chemical stability requirements, and the treatment of blast furnace slag has environmental pollution problems.
Clay sand is prepared by waste such as blast furnace slag, kaolin and red clay. Through grinding, mixing, granulation, drying and sintering processes, low-cost ceramic sand that meets the requirements of petroleum fracturing proppants is prepared.
The resource utilization of blast furnace slag has been realized, the production cost of clay sand has been reduced, and the clay sand that meets the requirements of petroleum fracturing proppant is provided. It has low density, high compressive strength and high temperature resistance chemical stability, which solves the problem of petroleum The high fracturing construction cost and the difficulty of blast furnace slag treatment.
Smart Images

Figure CN119191870A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of ceramsite sand, and in particular to a method for preparing ceramsite sand based on blast furnace slag, kaolin and red clay. Background Art
[0002] The general requirements for strength and density of petroleum fracturing proppants are as follows:
[0003] 1. Compressive strength and wear resistance: ceramsite proppants should be able to withstand pressures at different depths (such as 52MPa, 69MPa, 86MPa, 102MPa) and maintain high strength. 2. Low density: The relative density of proppant particles should be low to facilitate pumping into the well. Apparent density or volume density is a commonly used expression method. For example, quartz sand may be 1.76g / cm 3 The ideal proppant density should be as low as possible to reduce pumping difficulty, equipment wear and fracturing costs. The apparent density of the proppant is less than 2.75g / cm 3 3. High temperature resistance and chemical stability: The proppant particles do not react chemically with the fracturing fluid and reservoir fluid at a temperature of 200°C, and the maximum allowable acid solubility should be less than 7%.
[0004] In the existing technology, petroleum fracturing proppants generally use quartz sand, ceramsite, coated proppants or ultra-low density ceramic fracturing proppants. These products have various disadvantages to a greater or lesser extent. For example, quartz sand has a high density (bulk density ≥ 1.5g / cm 3 ), resulting in poor suspension performance and conductivity, making the fracturing construction cost high and the fracturing area small. The disadvantage of ceramsite is that it is easy to accumulate at the fracture port, which has a great impact on the performance of the sand-carrying fluid, while the disadvantage of the coated proppant is that the manufacturing process is complicated and the cost is high. At present, ceramsite sand (ceramic particles) plays an important role in many fields due to its unique physical and chemical properties, such as building insulation, mechanical wear resistance, and road construction, and its application prospects are becoming more and more broad and diversified. However, due to the special requirements of the oil industry for strength, density, high temperature resistance and chemical properties, the manufacturing cost of ceramsite sand used in oil fracturing proppants is high and it is difficult to promote.
[0005] Blast furnace slag is an important waste generated during the steelmaking process. Its hazards mainly include: environmental pollution, soil and water pollution, dust hazards, threats to human health and the growth and survival of plants and animals. Some companies have a high titanium content (about 8%) in blast furnace slag, which will have an adverse effect on the quality of cement, such as weakening the strength of cement, reducing cement durability, etc., resulting in prolonged cement setting time, etc. It cannot be used in cement preparation and can only be discarded as solid waste. The development of blast furnace slag treatment technology is an inevitable requirement for the sustainable development of the steel industry. At present, there is an urgent need for green methods that can be used for large-scale treatment.
[0006] In view of the above problems, the present invention proposes a method for preparing expanded clay sand based on blast furnace slag, kaolin and red clay, which can effectively solve the problem of resource treatment of blast furnace slag, and utilize the above waste to manufacture low-cost expanded clay sand, which has excellent indicators and can be used as an oil fracturing proppant.
[0007] The main components of blast furnace slag are
[0008] CaO 41.018% <![CDATA[SiO2]]> 27.041% <![CDATA[Al2O3]]> 12.138% MgO 8.316% <![CDATA[TiO2]]> 7.355% <![CDATA[SO3]]> 2.755% <![CDATA[Fe2O3]]> 0.441% <![CDATA[K2O]]> 0.356% MnO 0.220% Cl 0.169% SrO 0.106% <![CDATA[ZrO2]]> 0.041% <![CDATA[Cr2O3]]> 0.037% <![CDATA[Y2O3]]> 0.007%
[0009] 4. The main components of kaolin are
[0010] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[TiO2]]> 52±2% 45±2% <0.4% <0.4% <0.2% <0.04% <0.1% <1%
[0011] 5. The main components of red clay are
[0012] <![CDATA[SiO2]]> 66.273%
[0013] The specific component test results are shown in the table below
[0014] Summary of the invention
[0015] In view of the above technical problems, the purpose of the present invention is to provide a method for preparing expanded clay sand based on blast furnace slag, kaolin and red clay, so as to solve the problem of resource treatment of blast furnace slag, and utilize the above waste to manufacture low-cost expanded clay sand for application as oil fracturing proppant.
[0016] To achieve the above object, the present invention provides the following solutions:
[0017] A method for preparing ceramsite sand based on blast furnace slag, kaolin and red clay, comprising the following steps:
[0018] S1 Preparation
[0019] Select blast furnace slag, kaolin, red clay and bentonite;
[0020] S2 grinding
[0021] Grind the kaolin, blast furnace slag, red clay and bentonite prepared in S1 respectively, with a grinding mesh size of 200 meshes;
[0022] S3 Hybrid
[0023] Determine the material ratio according to the hardness of the required ceramsite sand, and evenly mix the kaolin, blast furnace slag, red clay and bentonite powder according to the proportion;
[0024] S4 Granulation
[0025] Granulate the mixed materials
[0026] S5 Drying
[0027] Put the semi-finished product after granulation into a drying oven, set the temperature to 120-150℃, and dry it for 1-3h to obtain raw pellets;
[0028] S6 Sintering
[0029] The dried green pellets are sintered at high temperature, and the sintering process is as follows:
[0030] 10-30min from room temperature to 400℃, 20-40min from 400℃ to 900℃, 20-40min from 900℃ to 1200℃, keep at 1200℃ for 60-90min, then reduce to room temperature;
[0031] S7 screening, grading and packaging after being released from the furnace
[0032] The ceramsite sand produced in step 6 is further sieved using sieves of different mesh sizes and graded and packaged according to diameter.
[0033] Specifically, the equipment selected in step S2 is a vibration mill, and the grinding time is 15-30 minutes. The mixing equipment selected in step S3 is a grinding machine. The drying oven selected in step S5 is an electric constant temperature blast drying oven. The high temperature sintering equipment in step S6 is a high temperature furnace. The sieves used for grading in step S7 are stainless steel sieves of different mesh sizes.
[0034] Specifically, in step S4, a disc granulation method is used, the mixed material is placed in a disc, and sprayed with atomized water intermittently to make the material adhere. When the radius of the produced sphere reaches a predetermined requirement, the granulation is stopped.
[0035] Specifically, the sintering in step S6 is controlled as follows: 20 min from room temperature to 400° C., 30 min from 400° C. to 900° C., 30 min from 900° C. to 1100° C., maintaining at 1100° C. for 60-90 min, and then cooling to room temperature.
[0036] Specifically, the weight ratio of the blast furnace slag, the kaolin and the red clay in step S3 is 4:3:0.5 or 4:3:1 or 4:3:2 or 4:3:3 or 4:3:4.
[0037] Specifically, the bentonite added as a binder has a weight percentage of 5.66%.
[0038] Specifically, the compressive strength of ceramsite sand is calculated by the following formula:
[0039]
[0040] In the formula, y: hardness value of expanded clay sand, x: addition ratio of kaolin.
[0041] Specifically, the method is suitable for making ceramsite sand for petroleum fracturing.
[0042] The invention has the following beneficial effects: the utilization of blast furnace slag waste is realized, and the ceramsite sand produced by the method has lower production cost as a petroleum fracturing proppant and is popularizable. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 Flow chart of the method of the present invention.
[0045] Figure 2 It is a curve diagram between temperature change and time during sintering process.
[0046] Figure 3 This is a photo of expanded clay sand with a diameter of 0.1-0.5 mm. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0049] A method for preparing ceramsite sand based on blast furnace slag, kaolin and red clay, comprising the following steps:
[0050] S1 Preparation
[0051] Select blast furnace slag, kaolin, red clay and bentonite;
[0052] S2 grinding
[0053] Grind the kaolin, blast furnace slag, red clay and bentonite prepared in S1 respectively, with a grinding mesh size of 200 meshes;
[0054] S3 Hybrid
[0055] Determine the material ratio according to the hardness of the required ceramsite sand, and evenly mix the kaolin, blast furnace slag, red clay and bentonite powder according to the proportion;
[0056] S4 Granulation
[0057] Granulate the mixed materials;
[0058] S5 Drying
[0059] Put the semi-finished product after granulation into a drying oven, set the temperature to 120-150℃, and dry it for 1-3h to obtain raw pellets;
[0060] S6 Sintering
[0061] The dried green pellets are sintered at high temperature, and the sintering process is as follows:
[0062] 10-30min from room temperature to 400℃, 20-40min from 400℃ to 900℃, 20-40min from 900℃ to 1200℃, keep at 1200℃ for 60-90min, then reduce to room temperature;
[0063] S7 screening, grading and packaging after being released from the furnace
[0064] The ceramsite sand produced in step 6 is further sieved using sieves of different mesh sizes and graded and packaged according to diameter.
[0065] Specifically, the equipment selected in step S2 is a vibration mill, and the grinding time is 15-30 minutes. The mixing equipment selected in step S3 is a grinding machine. The drying oven selected in step S5 is an electric constant temperature blast drying oven. The high temperature sintering equipment in step S6 is a high temperature furnace. The sieves used for grading in step S7 are stainless steel sieves of different mesh sizes.
[0066] Specifically, in step S4, a disc granulation method is used, the mixed material is placed in a disc, and sprayed with atomized water intermittently to make the material adhere. When the radius of the produced sphere reaches a predetermined requirement, the granulation is stopped.
[0067] Specifically, the sintering in step S6 is controlled as follows: 20 min from room temperature to 400° C., 30 min from 400° C. to 900° C., 30 min from 900° C. to 1100° C., maintaining at 1100° C. for 60-90 min, and then cooling to room temperature.
[0068] According to the above steps, five experiments were conducted for different proportions of blast furnace slag, kaolin, red clay and bentonite. The experimental proportions are shown in the following table:
[0069] Serial number Total amount / g Kaolin / g Blast furnace slag / g Red clay / g Proportion Bentonite / g 1 26.5 13.3 10 1.7 4:3:0.5 1.5 2 26.5 12.5 9.4 3.1 4:3:1 1.5 3 26.5 11.1 8.3 5.6 4:3:2 1.5 4 26.5 10 7.5 7.5 4:3:3 1.5 5 26.5 9.1 6.8 9.1 4:3:4 1.5
[0070] In the above five groups of experiments, the weight percentage of the bentonite added was about 5.66%.
[0071] The compressive strength of ceramic particles with a diameter of 2.0-2.5 mm was tested using an electronic universal testing machine. The results are as follows:
[0072]
[0073]
[0074] According to the above results, the hardness value of kaolin content X and compressive strength Y is fitted and calculated. When 0.36≤X≤0.53, the kaolin content and compressive strength show a certain Gaussian function curve relationship:
[0075]
[0076] Where y: hardness value of ceramsite sand x: addition ratio of kaolin
[0077] It can be seen from the above five groups of experimental results that when the ratio of blast furnace slag, kaolin, and red clay is 4:3:2, the compressive strength of ceramsite sand is the highest. However, since kaolin is a restricted resource among the four materials involved in the present invention, and its main production area is Jingdezhen, in order to control production costs, its dosage needs to be strictly controlled. According to actual needs, the above-fitted hardness calculation formula can be used to reasonably select the dosage of kaolin while meeting the use requirements. Red clay is a local resource in Chengde and is easy to obtain.
[0078] The details not described in detail in the present invention are all conventional technical means known to those skilled in the art.
[0079] In the description of the present invention, it should be understood that the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0080] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing ceramsite sand based on blast furnace slag, kaolin and red clay, characterized in that: The following steps are involved: S1 Preparation Select blast furnace slag, kaolin, red clay and bentonite; S2 grinding Grind the kaolin, blast furnace slag, red clay and bentonite prepared in S1 respectively, with a grinding mesh size of 200 meshes; S3 Hybrid Determine the material ratio according to the hardness of the required ceramsite sand, and evenly mix the kaolin, blast furnace slag, red clay and bentonite powder according to the proportion; S4 Granulation Granulate the mixed materials; S5: Drying Put the semi-finished product after granulation into a drying oven, set the temperature to 120-150℃, and dry it for 1-3h to obtain raw pellets; S6 Sintering The dried green pellets are sintered at high temperature, and the sintering process is as follows: 10-30min from room temperature to 400℃, 20-40min from 400℃ to 900℃, 20-40min from 900℃ to 1200℃, keep at 1200℃ for 60-90min, then reduce to room temperature; S7 screening, grading and packaging after being released from the furnace The ceramsite sand produced in step 6 is further sieved using sieves of different mesh sizes and graded and packaged according to diameter.
2. The method for preparing ceramsite sand based on blast furnace slag, kaolin and red clay according to claim 1, characterized in that: The equipment used in step S2 is a vibration mill, and the grinding time is 15-30 minutes. The mixing equipment used in step S3 is a grinding machine. The drying oven used in step S5 is an electric constant temperature blast drying oven. The high temperature sintering equipment in step S6 is a high temperature furnace. The sieves used for grading in step S7 are stainless steel sieves of different mesh sizes.
3. The method for preparing ceramsite sand based on blast furnace slag, kaolin and red clay according to claim 1, characterized in that: In step S4, a disc granulation method is used, wherein the mixed material is placed in a disc, and sprayed with atomized water intermittently to make the material adhere. When the radius of the produced sphere reaches a predetermined requirement, the granulation is stopped.
4. The method for preparing ceramsite sand based on blast furnace slag, kaolin and red clay according to claim 1, characterized in that: The sintering in step S6 is controlled as follows: 20 minutes from room temperature to 400°C, 30 minutes from 400°C to 900°C, 30 minutes from 900°C to 1100°C, maintaining at 1100°C for 60-90 minutes, and then cooling to room temperature.
5. The method for preparing ceramsite sand based on blast furnace slag, kaolin and red clay according to any one of claims 1 to 4, characterized in that: The weight ratio of the blast furnace slag, the kaolin and the red clay in the step S3 is 4:3:0.5 or 4:3:1 or 4:3:2 or 4:3:3 or 4:3:
4.
6. The method for preparing ceramsite sand based on blast furnace slag, kaolin and red clay according to claim 5, characterized in that: The bentonite added as a binder has a weight percentage of 5.66%.
7. The method for preparing ceramsite sand based on blast furnace slag, kaolin and red clay according to claim 5, characterized in that: The compressive strength of ceramsite sand is calculated by the following formula: In the formula, y: hardness value of expanded clay sand, x: addition ratio of kaolin.
8. The method for preparing ceramsite sand based on blast furnace slag, kaolin and red clay according to claim 5, characterized in that: It is suitable for making ceramsite sand for oil fracturing proppant.
